The evaluative image of the city through the lens of social media: case study of Melbourne CBD - Motamed, Bahareh; Mahmoudi Farahani, Leila (Journal of Architecture and Urbanism, 2018)
The ubiquitous of smartphones and access to social media provide a new way of interacting with urban environments. The archived and shared images on social media not only indicate users’ interest but also they embody what users want to remember from a city. To investigate the evaluative image of a city through published images, Melbourne CBD has been selected as a case study. An in-depth survey of 460 geotagged photos from CBD in Flickr, 500px and Instagram (during 2014), provides an opportunity for city planners and urban designers to transform the image of a city to be more likeable, meaningful.